The Use of King Kevin TikTok Videos for Short Story Writing Learning at SMPN 7 Jambi City - Desmarleni Putri; Hary Soedarto Haryono; Rahmawati (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the use of TikTok videos from King Kevin's account for students' short story writing learning. This study used a qualitative method with a case study approach conducted in the even semester of the 2023/2024 academic year. The population of this study was 38 students of class VIII C at SMP Negeri 17 Jambi City who participated in short story writing learning using TikTok videos from King Kevin's account. The sample consisted of 29 students selected using a purposive sampling technique. Research data were collected using observation guidelines, interview guidelines, and test instruments. Data analysis techniques used data reduction, data presentation, and conclusion drawing. The results of the study showed that the use of TikTok videos in learning to write short stories went well and it can be said that the learning process and atmosphere were achieved well. From the procedures carried out, it was in accordance with the lesson plan and teaching modules that had been prepared by the teacher before starting the lesson. From the learning process and the results of students' short story writing exercises, using TikTok videos from King Kevin's account was considered very good for students in learning to write short stories, as evidenced by the students' enthusiasm and concentration in carrying out the learning process and the results of their exercises. The average score of class VIII C students is 85.59 and is in the very good category and more than half of the students, namely 62.07%, are in the very good category.